RESPON SISWA TERHADAP PEMBELAJARAN MATEMATIKA DENGAN KEMAMPUAN MATEMATIK HABITS OF MIND - Nurpalihah Hasanah; Ratni Purwasih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to determine: student responses and the effect of learning mathematics with the ability of habits of mind in class VII MTs students. Az-Zahra Selacau. The method used in this study is a quantitative method with a descriptive approach. The subjects of this study were all students of class VII MTs. Az-Zahra Selacau for the 2020/2021 academic year, while the research sample consisted of 25 students. The data collection technique was carried out by providing an instrument in the form of a student response questionnaire to learning mathematics which consisted of 32 statements, with 16 indicators of habits of mind. The processing technique used is Microsoft Excel. The average student answers to statements in number 1 and number 11 is the highest average of 3.2. While statement number 15 is a statement with the lowest average of 2.4. Based on the criteria for the habits of mind score in table 2, the habits of mind of MTs students. Az-Zahra Selacau class VII is in the positive category.